2018
DOI: 10.3892/ijmm.2018.3509
|View full text |Cite
|
Sign up to set email alerts
|

GLP‑1R agonists ameliorate peripheral nerve dysfunction and inflammation via p38 MAPK/NF‑κB signaling pathways in streptozotocin‑induced diabetic rats

Abstract: The present study aimed to investigate the mechanism of glucagon‑like peptide‑1 receptor (GLP‑1R) agonists in the progression of diabetic peripheral neuropathy (DPN) in streptozotocin (STZ)‑induced diabetic rats, through inflammatory signaling pathways. The DPN rat model was generated by intraperitoneal injection of STZ and then treated with the GLP‑1R agonist liraglutide or saline for 8 weeks. These animals were randomly divided into 4 groups (10 rats in each): The normal control + saline group, the normal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Exendin-4, a peptide agonist of GLP-1 attenuated pain-induced cognitive impairment through the alleviation of neuroinflammation in NP rats [ 28 ]. In addition, DPP-4i like sitagliptin and GLP-1 analog liraglutide are shown to induce axonal regrowth and locomotor functional repair through the restoration of spinal GLP-1R levels in SCI rats [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exendin-4, a peptide agonist of GLP-1 attenuated pain-induced cognitive impairment through the alleviation of neuroinflammation in NP rats [ 28 ]. In addition, DPP-4i like sitagliptin and GLP-1 analog liraglutide are shown to induce axonal regrowth and locomotor functional repair through the restoration of spinal GLP-1R levels in SCI rats [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Feldman et al found that nerve growth factor-induced mechanical allodynia in the db/db mouse was mediated by the phosphorylation of p38 and the upregulation of multiple inflammatory mediators in lumbar dorsal root ganglia [19]. Several studies have demonstrated that inhibitors targeting the p38/MAPK pathway ameliorated inflammatory processes and neurological deficits in experimental DPN [20][21][22]. While it has been indicated that the regulatory function of p38 kinases on inflammatory processes is mainly through p38α (and probably β), the role of p38γ and p38δ in inflammation is unknown [17].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that GLP-1 agonists inhibit NLRP3 inflammasome activation through sirtuin1 signaling to alleviate cardiovascular impairment (44,45). Another study found that GLP-1 agonists alleviated inflammation and attenuated peripheral nerve injury via the p38 MAPK/NF-κB pathway (46). A previous study also indicated that ibuprofen has antiepileptic and neuroprotective effects through the cyclooxygenase-2/NLRP3 pathway in PTZ-kindled mice (18).…”
Section: Discussionmentioning
confidence: 96%